National health insurance - O Brolchain, R. (Statistical and Social Inquiry Society of Ireland, 1943)
It is necessary, in any consideration of the National Health Insurance scheme, to bear in mind a number of important factors. (a) It was established initially to relieve the excessive demands on the Poor Law, following the report of the famous Poor Law Commission of 1909. (b) The basic Act which governs health insurance is an English Act, passed for both England and Ireland in 1911. (c) In its application to Ireland, the Act was robbed of an essential feature?the provision of free medical treatment for insured persons. (d) The scheme is based on the principle that every insured person (with a slight difference as between men and women) pays the same weekly contribution and receives the same weekly benefit, irrespective of earnings. (e) No benefit is payable during incapacity coming under the provisions of the Workmen's Compensation Act, the Employer's Liability Acts, or the Common Law. (f) No allowance was made for the predominance of agricultural employment in Ireland as compared with industrial employment in England.
Symposium on Irish Social Services
Read March 5th 1943
Keywords: Health insurance; 314.15